Direct Comparison of Solution and Gas-phase Reactions of the Three Distonic Isomers of the Pyridine Radical Cation With Methanol - Widjaja, Fanny (2012)
In order to directly compare the reactivity of positively charged carbon-centered aromatic σ-radicals toward methanol in solution and in the gas phase, the 2-, 3-, and 4-dehydropyridinium cations (distonic isomers of the pyridine radical cation) were generated by ultraviolet photolysis of the corresponding iodo-precursors in a mixture of water and methanol at varying pH. The reaction mixtures were analyzed by using liquid chromatography/mass spectrometry. Hydrogen atom abstraction was the only reaction observed for the 3- and 4-dehydropyridinium cations (and –pyridines) in solution. This also was the major reaction observed earlier in the gas phase. Depending on the pH, the hydrogen atom can be abstracted from different molecules (i.e., methanol or water) and from different sites (in methanol) by the 3- and 4-dehydropyridinium cations/-pyridines in solution. In the pH range of 1 – 4, the methyl group of methanol is the main hydrogen atom donor site for both 3- and 4-dehydropyridinium cations (just like in the gas phase). At higher pH, the hydroxyl groups of water and methanol also act as hydrogen atom donors. This finding is rationalized by a greater abundance of the unprotonated radicals that preferentially abstract hydrogen atoms from the polar hydroxyl groups. The percentage yield of hydrogen atom abstraction by these radicals was found to increase with lowering the pH in the pH range of 1.0-3.2. This pH effect is rationalized by polar effects: the lower the pH, the greater the fraction of protonated (more polar) radicals in the solution. This finding is consistent with previous results obtained in the gas phase and suggests that gas-phase studies can be used to predict solution reactivity, but only as long as the same reactive species is studied in both experiments. This was found not to be the case for the 2-iodopyridinium cation. Photolysis of this precursor in solution resulted in the formation of two major addition products, 2-hydroxy- and 2-methoxypyridinium cations, in addition to the hydrogen atom abstraction product. These addition products were not observed in the earlier gas-phase studies on 2-dehydropyridinium cation. Their observation in solution is explained by the formation of another reactive intermediate, the 2-pyridyl cation, upon photolysis of 2-iodopyridinium cation (and 2-iodopyridine). The same intermediate was observed in the gas phase but it was removed before examining the reactions of the desired radical, 2-dehydropyridinium cation (which cannot be done in solution).